Exploring the interplay between a loving pedagogy, creativity, and work engagement among EFL/ESL teachers: A multinational study - Derakhshan, Ali; Greenier, Vincent; Fathi, Jalil (Current psychology (New Brunswick, N.J.), 2023)
This study investigates the validity of three psychometric scales—the Disposition towards Loving Pedagogy (DTLP), Teaching for Creativity Scale (TCS), and Utrecht Work Engagement Scale (UWES)—to uncover the relationship between these constructs with a multinational cohort of language teachers. The results obtained from Exploratory Factor Analysis and Confirmatory Factor Analysis confirmed the psychometric properties of the three scales. The hypothesized model for the relationship between participants’ DTLP, TCS, and their UWES revealed that although both predictor variables significantly predicted UWES, TCS was a stronger predictor for UWES. The model was also tested for measurement invariance across ethnicity and gender. By drawing on the findings obtained in this study, future language researchers are aided to employ the three revalidated scales in their research undertakings on a cross- or multi-cultural scale, and increase expansion of culture-centered research on various teacher personality variables with the aim of precipitating language teachers’ continuing professional development.